Are Alzheimer’s disease, hypertension, and cerebrocapillary damage related? - Farkas, Eszter; De Vos, Rob A.I.; Steur, Ernst N.H.Jansen; Luiten, Paul G.M. (Neurobiology of aging, 2000)
Alzheimer’s disease (AD) patients are often subject to vascular dysfunction besides their specific CNS pathology, which warrants further examination of the interaction between vascular factors and the development of dementia. The association of decreased cerebral blood flow (CBF) or hypertension with AD has been a target of growing interest. Parallel with physiological changes, the cerebral capillaries in AD are also prone to degenerative processes. The microvascular abnormalities that are the result of such degeneration may be the morphological correlates of the vascular pathophysiology pointing to a compromised nutrient transport through the capillaries. Animal models have been developed to study the consequences of hypertension and reduced CBF. Spontaneously hypertensive rats are widely used in hypertension research whereas ligation of the carotid arteries has become a method to produce cerebral hypoperfusion. Based on these models, we propose a relationship between hypertension, cerebral hypoperfusion, cerebral capillary malformation and cognitive decline as it occurs in AD. We suggest that the above conditions are functionally related and can contribute to the progression of AD.